1971
DOI: 10.1111/j.1469-185x.1971.tb01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Sheep Red Blood Cell

Abstract: Summary 1. There are 7 well‐established red‐cell antigen (blood group) loci. The R‐O system has 3 phenotypes, R, O and i, identified by the ‘naturally occurring’ antibodies, anti‐R and anti‐O. The R and O substances are also present in soluble form in some body secretions. The expression of R and O is controlled by a dominant gene I, epistatic in effect, at an independent locus from that of R. The systems, A, C, M‐L, B, D and X‐2 are identified by means of ‘immune‐type’ antibodies, and several of the loci have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
3

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 156 publications
1
27
0
3
Order By: Relevance
“…Such dimorphism of the cellular ion concentrations has been extensively used for studies of ion transport in cell membranes, although their clinical and physiological roles are not well understood [12,14,16]. Thus, the HK dogs are expected to provide new information to researchers in this field of study.…”
mentioning
confidence: 99%
“…Such dimorphism of the cellular ion concentrations has been extensively used for studies of ion transport in cell membranes, although their clinical and physiological roles are not well understood [12,14,16]. Thus, the HK dogs are expected to provide new information to researchers in this field of study.…”
mentioning
confidence: 99%
“…This phenomenon is possible because the ATPase enzyme intimately involved in sodiumpotassium pump mechanism from the level of cell membrane [22]. The goats represent the second species after sheep, on the extent of potassium polymorphism investigation.…”
Section: Disscussionmentioning
confidence: 99%
“…Many studies have noted distributional discontinuity of potassium in the blood of animals, which has suggested that this chemical element presents polymorphism having genetic determinism [2,3,5,7,810,11,13,17,21,22]. The polymorphism of erythrocyte potassium was for first time detected in sheep by Evans and King [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most animal cells maintain high internal potassium and low sodium ion concentration due to the activity of the sodium/ potassium-ATPase (Na/ K-ATPase) pump in the membrane, which uses energy derived from the hydrolysis of ATP to accumulate potassium ions and expel sodium ions. The enzyme ATPase is intimately involved in the potassium or sodium-pump mechanism (TUCKER, 1971). EVANS (1954) reported that erythrocyte potassium concentration varied in sheep and two distinct types could be found in British breed.…”
Section: Introductionmentioning
confidence: 99%